The sustainable sites handbook : a complete guide to the principles, strategies, and practices for sustainable landscapes - Calkins, Meg. (Hoboken, New Jersey : John Wiley & Son, Inc., 2012)
"This official reference guide to the Sustainable Sites Initiative Rating System contains information on principles, strategies, technologies, tools, and best practices for sustainable site design applicable to any type of designed landscape, with or without buildings, ranging from shopping malls, streetscapes, subdivisions, corporate and academic campuses, transportation corridors, parks and recreation areas, all the way to single family homes. Equally useful as a guide to achieving SSI credits, or as a guide to independent pursuit of sustainable sites, it offers in-depth coverage on important "green" topics"-- | "This book will be the official reference guide to Sustainable Sites Initiative Rating System, the first national rating system for sustainable landscapes"--
Foreword -- Letter from SITES Partners -- 1. Introduction -- 2. Predesign: Site selection, assessment, and planning -- 3. Site design: water -- 4. Site design: vegetation -- 5. Site design: soils -- 6. Site design: materials and resources -- 7. Human health and well-being for sustainable sites -- 8. Operations, maintenance, monitoring, and stewardship
Includes bibliographical references and index.
Keywords: LANDSCAPE ECOLOGY